Serum Levels of the C-terminal Fragment of Fibroblast Growth Factor 23 (C-FGF23) and Hepcidin in Patients with Hemodialysis Undergoing Treatment with a Proline Hydroxylase Domain (PHD) Inhibitor - Motomiya, Yoshihiro; Kaneko, Yoshiteru; Motomiya, Yasuki; Higashimoto, Yuichiro (Journal of Clinical Nephrology, 2024)
Background: We previously reported, for the first time, serum levels of the C-terminal fragment of fibroblast growth factor 23 (C-FGF23) in patients undergoing hemodialysis (HD). Most HD patients have undergone treatment with either recombinant erythropoietin (r-EPO) or hypoxia-inducible factor (HIF) proline hydroxylase domain (PHD) inhibitor, both of which stimulate FGF23 production and cleavage. Methods: This cross-sectional observational study involved analyzing measuring FGF-related parameters and comparing results for subgroups of patients who received either r-EPO and or a PHD inhibitor. Results: No significant difference was observed for iron-related parameters or serum hepcidin levels in both subgroups of patients. Significant differences were found for certain FGF-23-related parameters. Conclusion: Both FGF23 production and cleavage were stimulated more in patients treated with the PHD inhibitor than in patients treated with r-EPO.